Reframing the discourse and rhetoric of language testing and assessment for the public square. (January 2023) - Taylor, Lynda
As applied linguists and language testers, we are in the business of "doing language". For many of us, language learning is a lifelong passion, and we invest similar enthusiasm in our language assessment research and testing practices. Language is also the vehicle through which we communicate that enthusiasm to others, sharing our knowledge and experience with colleagues so we can all grow in understanding and expertise. We are actually quite good at communicating within our own community. But when it comes to interacting with people beyond our own field, are we such effective communicators? Wider society—politicians, journalists, policymakers, social commentators, teachers, and parents—all seem to find assessment matters hard to grasp. And I am not sure we as language testers do much to help them. So I find myself wondering why that is? Is it that our language is too specialised, or overly technical? Do we choose unhelpful words or images when we talk about testing? Worse still, do we sometimes come across as rather arrogant or patronising, perhaps even irrelevant to non-specialists' needs and concerns? If so, could we perhaps consider reframing our discourse and rhetoric in future to improve our communicative effectiveness, and how might we do that?